RESPON AGRONOMIS BAWANG MERAH (Allium cepa L.) VARIETAS BATU IJO TERHADAP APLIKASI DOSIS PUPUK KANDANG AYAM DAN KONSENTRASI PUPUK ORGANIK CAIR - Lily Soemarti; Yudi Yusdian; Erfan; Cep Okki Oktaviandi; Rafly Al Ghifari Ramdhan (Program Studi Agroteknologi Faperta UNIBBA, 2026)
This study aims to determine the effect of interaction between Chicken Manure and Liquid Organic Fertilizer on the growth and yield of shallots (Allium cepa L.) Batu Ijo variety and to determine the best effect between Chicken Manure and Liquid Organic Fertilizer on the growth and yield of shallots (Allium cepa L.) Batu Ijo variety. The implementation of this experiment was carried out in Margahurip Village, Banjaran District, Bandung Regency, West Java Province. This study used an experimental method, with a Factorial Randomized Block Design consisting of 2 treatment factors, namely chicken manure and liquid organic fertilizer. Chicken Manure consists of k1 (0 tons/ha) k2 (10 tons/ha) k3 (20 tons/ha), while Liquid Organic Fertilizer consists of c1 (0 ml/l) c2 (3 ml/l) c3 (6 ml/l). The results of the study showed that there was no interaction between the dose of chicken manure and the concentration of liquid organic fertilizer on the growth and yield of shallots (Allium cepa L.) Batu Ijo variety. The dose of chicken manure (k3) of 20 tons/ha had a better effect on plant height at the age of 21 and 35 DAP. The dose of chicken manure (k3) of 20 tons/ha had a better effect on the weight of wet bulbs per plot and the diameter of wet bulbs.